Optimization of digital terrain model for its application in forestry - M. Klimánek (Journal of Forest Science, 2006)
Digital terrain model (DTM) represents a very important geospatial data type. In the CzechRepublic, the most common digital contour data sources are the Primary Geographic Data Base (ZABAGED), the Digital Ground Model (DMÚ25) and eventually the Regional Plans of Forest Development (OPRL). In constructing regular raster DTM, the initial process requires interpolation between the points in order to estimate values in a regular grid pattern. In this study, constructions of DTM from the above-mentioned data were tested using several software products: ArcEditor 9.0, Atlas 3.8, GRASS 6.1, Idrisi 14.02 and TopoL 2001. Algorithm parameters can be optimized in several ways. In this sense a comparison of the first and second derivative of DTM and its real appearance in the terrain and a cross-validation procedure or terrain data measurements to compute and minimize the root mean square error values (RMSE) proved to be the most useful operations. The ZABAGED contour data provided the best results, with software specific algorithms for interpolations of contour data (ArcGIS Desktop Topo to Raster, Idrisi Kilimanjaro TIN).